Pengaruh Literasi Informasi terhadap Model Pembelajaran Problem Based Learning - Sunyianto, Sunyianto; Pasaribu, Ida M.; Zakiah, Diana M.; Azmi, M. Fadlul; Kerisman, Kerisman; Markus, Markus (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2024)
Information literacy is a critical skill that supports learning processes, especially in Problem-Based Learning (PBL) models, which emphasize critical thinking and problem-solving. This study aims to investigate the influence of information literacy on PBL models in vocational education at SMK Negeri 10 Medan. Using a quantitative descriptive method, the research involved 55 students, divided into experimental and control groups. The experimental group applied PBL, while the control group used conventional learning models. Results revealed a significant improvement in the information literacy skills of the experimental group, with pretest and posttest average scores increasing from 52.00 to 82.92, compared to the control group (pretest 51.50, posttest 79.63). Statistical analysis confirmed the significant impact of PBL on improving information literacy. The findings suggest that PBL enhances students' engagement, critical thinking, and ability to utilize information effectively. This research advocates for integrating PBL in educational curricula to foster higher-order thinking skills and better academic outcomes